ANALYSIS OF NURSING CARE FOR THE ELDERLY WITH APPLICATION OF WARM CITRONELLA COMPRESS TO TREAT ACUTE PAIN RHEUMATOID ARTHRITIS IN A NURSING HOME JAMBANGAN SURABAYA - Rohmawati, Siti; Zahroh, Chilyatiz; Nurjannah, Siti; Muhith, Abdul (Nurse and Holistic Care, 2024)
Introduction: Rheumatoid arthritis (RA) is an inflammatory disease with symptoms of stiffness and pain in the joints. Individuals typically experience pain and weakness in specific body parts, namely the hands, feet, knees, and shoulders. Complaints of pain characterized by cramps and tingling are sensory complaints. If pain complaints are not treated or medication is not given, the impact will be disruption of physical activity, disruption of sleep patterns, and also disruption of comfort. Objective: To provide an overview of nursing care for the elderly by applying warm lemongrass compresses to treat rheumatoid arthritis pain at the Surabaya Nursing Home. Methods: The research method used is a case study. The subject of this research is Mr. B who is 61 years old with acute pain problems and was given warm lemongrass compresses for three days. Data collection techniques in this research were carried out by interviews and direct observation of patients using gerontic nursing care sheets and pain scale measurements using the numerical rating scale (NRS) method. Results: The results obtained by the client did not appear to be grimacing and were careful with his movements, complaints of pain from scale 2 (moderately increased) to scale 1 (decreased), grimaces from scale 2 (moderately increased) to scale 1 (decreased), restlessness from scale 2 (moderately increased) to scale 1 (decreased), difficulty sleeping from scale 2 (moderately increased) to scale 1 (decreased). Conclusions: Applying warm lemongrass compresses can reduce the intensity of pain complaints improve blood circulation and relax the patient.  Therefore, we hope that nurses will apply warm lemongrass compresses to patients with rheumatoid arthritis.